Impact of Digital Storytelling for Developing Oral Communication Skills, Digital Literacy, and Learning Motivation Among Pre-service Elementary Teachers - Setiawan, Dadan; Masuwd, Mowafg Abrahem; Maliki, Noval; Laily, Idah Faridah; Fitriyani, Yani (International Journal of Educational Qualitative Quantitative Research, 2023)
In the digital era, oral communication skills, digital literacy, and learning motivation are crucial aspects of education. Digital storytelling is an innovative method that enhances speaking abilities and fosters creativity and active engagement among pre-service elementary teachers in learning. This study aims to explore the impact of digital storytelling in enhancing oral communication skills, digital literacy, and learning motivation among pre-service elementary teachers. A quasi-experimental design with a non-equivalent control group was employed. The sample consisted of 120 pre-service elementary teachers from the State Islamic Cyber University Syekh Nurjati Cirebon, selected through purposive sampling. The experimental group included 58 participants, while the control group comprised 62. Data were collected through oral communication tests, digital literacy questionnaires, and learning motivation surveys administered before and after the intervention. Instrument validity was assessed using content validity with two experts in education and technology, while reliability was measured using Cronbach’s Alpha. Data analysis involved T-tests and Cohen’s D effect size calculations. The findings indicate that digital storytelling significantly improved all three variables, with large effect sizes for oral communication skills (d = 2.21), digital literacy (d = 2.52), and learning motivation (d = 2.65). These results suggest that digital storytelling is an effective pedagogical tool for equipping pre-service elementary teachers with essential competencies in the digital era. This study recommends systematically integrating digital storytelling into pre-service elementary teacher education curricula, developing structured pedagogical scaffolding, and collaborating with partner schools to support skill application in teaching practice.